Construction and Standardization of Beauty Satisfaction Scale for Adolescents with Cleft Lip and Palate - Nandini Mannadath; Jayan C. (International Journal of Orthopedic Nursing and Practices, 2023)
This study outlines the methodology and findings of a study that aimed to create a tool for assessing adolescents with oral facial clefts’ levels of beauty satisfaction. The development of this tool includes a well-detailed literature survey, focus group discussion with adolescents with oral facial clefts, and the wide process of consultation with the cleft surgeon, orthodontist, pediatrician, and clinical psychologist. Further test construction includes planning of the scale, item preparation, try out, scoring, and item analysis. The beauty satisfaction scale consists of 20 statements in a five-point Likert scale which consists of both positive and negative items. for beauty satisfaction with the help of the guide. This tool is a promising tool in the field of oral-facial cleft with the utility of assessing the perception of beauty satisfaction among the cleft population.
Keywords: Beauty satisfaction scale; adolescent; cleft lip and palate; oral facial clefts